Model Order Reduction of Microactuators: Theory and Application - Arwed Schütz; Tamara Bechtold (Actuators, 2023)
This paper provides an overview of techniques of compact modeling via model order reduction (MOR), emphasizing their application to cooperative microactuators. MOR creates highly efficient yet accurate surrogate models, facilitating design studies, optimization, closed-loop control and analyses of interacting components. This is particularly important for microactuators due to the variety of physical effects employed, their short time constants and the many nonlinear effects. Different approaches for linear, parametric and nonlinear dynamical systems are summarized. Three numerical case studies for selected methods complement the paper. The described case studies emerged from the Kick and Catch research project and within a framework of the German Research Foundation’s Priority Program, Cooperative Multistable Multistage Microactuator Systems (KOMMMA).